Broadening of the range of extremity orthoses by use of a prepreg - Solntseva, Irina; Khmelevskaya, Iryna; Lukovenko, Oleksandr; Grishko, Yevgene; Belevtsova, Lyudmila (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
Creation of technologies for manufacturing prosthetic-orthopaedic products (POP) out of modern materials is one of priorities in the development of prosthetics. The Ukrainian Research Institute of Prosthetics, Prosthesis Making and Working Capacity Restoration created three types of such a material as prepreg with different deformation-strength properties. This variety of prepreg properties made it possible to design POP for lower extremities with good strength and service properties, which enable patients to control their movements in dynamics with regard for pathology peculiarities in each patient.